Kimmy Dora and the temple of Kiyeme - Domingo, Eugene; Dantes, Dingdong; Marudo, Zanjoe; Bernal, Joyce A.; De Jesus, Vincent A.; Santos-Consio, Charo; Santos, Malou; Pascual, Piolo Jose N. (Quezon City Spring Films, 2012)
The Story continues from where the first installment ended. Kimmy and Dora are now deeply in love with their respective boyfriends, gentlemanly farmer Barry (Zanjoe Marudo) and nerby yuppie Johnson (Dingdong Dantes). The new adventure begins when the sisters join their father Luisito (Ariel Ureta) on a trip to his native homeland Korea. There, the patriarch reveals that one of them has to marry into the Sang clan as fulfillment of a promise made in their families' past. However, neither Kimmy nor Dora agrees to their father's request. A mysterious Korean ghost (Alodia Gosiengfiao) follows them back to Manila, haunting and claiming the souls of the men in their lives. The only way to stop the haunting is to finally give in to their father's request or fight off the malevolent spirit.
VCD
Executive producers, Charo Santos-Concio, Malou Santos, Piolo Jose N. Pascual ; story and screenplay, Chris Martinez ; musical director, Vincent A. De Jesus ; director, Bb. Joyce A. Bernal.
Eugene Domingo, Dingdong Dantes, Zanjoe Marudo.
Keywords: Kimmy Dora and the temple of Kiyeme (Motion picture).; Comedy films; Horror films